42 Bittersweet life in the face of loss: the experience of parenteral nutrition for women with ovarian cancer and their relatives. Issue 3 (1st September 2018) - Sowerbutts, Anne Marie; Lal, Simon; Clamp, Andrew; Jayson, Gordon C; Todd, Chris; Raftery, Anne-Marie; Hardy, Lisa; Sutton, Eileen; Sremanakova, Jana; Burden, Sorrel
Abstract : Introduction: Patients with advanced ovarian cancer can develop bowel obstruction. Oral intake is limited in these patients and home parenteral nutrition (PN) may be used to meet nutritional requirements. Aim: To explore patient and family experience of home PN. Method: Ninety-three longitudinal in-depth interviews were conducted with 20 women with ovarian cancer and inoperable bowel obstruction receiving PN, their lay-carers and healthcare professionals. Interviews were transcribed verbatim and analysed thematically influenced by the techniques of Van Manen (1990). Results: Women and their relatives viewed PN as increasing length of life and allowing the women to live at home with some normality. However, the treatment was not without problems which may not be acknowledged by healthcare professionals. These included difficulties with activities of daily living, incursions of physical freedom as patients were attached to heavy PN bags and dealing with the bureaucracy associated with PN. Healthcare professionals were working to a patient-centred rather than a family-centred palliative care model, which could be problematic for some families with frail relatives. However, carers coped but emotionally were often left in a vulnerable state. Conclusions: For patients and carers the treatment was a life line and they appreciated the extra time the women received. However this was gained through many losses which healthcare professionals need to portray accurately and implement a family-centred palliative care model when appropriate. Nevertheless, patients are prepared to suffer losses in order to continue living. Reference: . Van Manen M. Researching lived experience: Human science for an action sensitive pedagogy 1990. London Ont: Althouse Press.